2009
DOI: 10.1007/s11999-008-0574-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Suction Device on Fixation of a Cemented Cup using RSA

Abstract: The quality of technique used at the time of socket cementation is crucial in ensuring a durable longterm result of the implant. We asked whether a new instrument, an aspirator retractor introduced into the wing of the ilium before socket preparation and cementation, would enhance cement fixation as defined by RSA and radiographic examination. We randomized 38 patients into two groups. The surgical technique was identical between the groups with the exception of the use of the aspirator retractor. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Thus, prevention of zone-1 radiolucency is of paramount importance. 26 To reduce the occurrence of radiolucent lines, drilling penetration holes for the cement, cleansing the bone bed of marrow and debris by pulsatile lavage, 27 minimising bleeding by the use of hypotensive anaesthesia, careful haemostasis with hydrogen peroxide solution 28 or adrenaline 29 using a sucker aspirator, 10,30 and prolonged application of a proprietary pressuriser 31 have all been recommended. As injection pressure of the cement is lower in the acetabulum than in the femur, the same inter-digitation cannot be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, prevention of zone-1 radiolucency is of paramount importance. 26 To reduce the occurrence of radiolucent lines, drilling penetration holes for the cement, cleansing the bone bed of marrow and debris by pulsatile lavage, 27 minimising bleeding by the use of hypotensive anaesthesia, careful haemostasis with hydrogen peroxide solution 28 or adrenaline 29 using a sucker aspirator, 10,30 and prolonged application of a proprietary pressuriser 31 have all been recommended. As injection pressure of the cement is lower in the acetabulum than in the femur, the same inter-digitation cannot be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The iliac sucker was used in the wing of the acetabulum to enhance cement penetration and clear blood from the cement-bone interface. 2,[9][10][11] The socket was then inserted 5 to 7 minutes after mixing of the Simplex cement at 20ºC, using the introducer and an axial pusher to drive the socket into the seated position. A greater force was needed to seat the cup as the flange approached the rim, because the pressure rose within the cement behind the cup.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Although fixation of the femoral component has been improved by compression of cement at low viscosity into restricted clean dry bone, there has been disproportionately little research on acetabular cementing technique. Keyholes were adopted to promote interference between cement and bone, and cement penetration into these enhanced by gunning in low viscosity cement at high pressure, and negative pressure from iliac suction and positive pressure from flanged cups have been introduced; however, clinical results have not significantly improved [1,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Cemented total hip arthroplasty (THA) is a globally successful intervention 1) . Long-term results for cemented implants has shown increased implant longevity and improved outcomes 1 2 3) . Long-term results have also demonstrated that the most widespread cause of failure is aseptic loosening 4 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the acetabular bone surface preparation has been recognized as an important process of generating a solid bone-cement interface 12 13) . The mechanism of action of this secure cementation technique is believed to prevent early fluid and debris penetration 3 12) . A wide spread method to achieve cemented acetabular fixation has been the introduction of reaming with retention of the subchondral bone plate (SCBP) for improved stability of fixation 14 15) .…”
Section: Introductionmentioning
confidence: 99%